2018
DOI: 10.2196/diabetes.8069
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Simulation to Change Outcome Expectancies and Intentions in Adults With Type 2 Diabetes: Within-Subjects Experiment

Abstract: In response to the statements "This website was informative" and "This website was not useful" (1-strongly agree to 7-strongly disagree), participants were generally positive. On average, participants felt that the website was informative (mean=2.9/7; SD 1.7) and disagreed that the site was not useful (mean= 5.2/7, SD=1.8).Finally, 394 participants provided qualitative feedback in the "Please provide any feedback you have on this website or study" text box. Here we report the coding for quotes in which all thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“… 21 Furthermore, Wu et al 22 reported a significant association with better self-management (diet, exercise, medication, blood sugar, and foot care over the past 7 days). Other studies by Williams and Bond 23 and Gibson et al 24 reported a similar relationship. When we consider outcome expectancy as a proxy for expected utility, there is a clear link between time preference and outcome expectancy in economic theory.…”
Section: Introductionsupporting
confidence: 53%
“… 21 Furthermore, Wu et al 22 reported a significant association with better self-management (diet, exercise, medication, blood sugar, and foot care over the past 7 days). Other studies by Williams and Bond 23 and Gibson et al 24 reported a similar relationship. When we consider outcome expectancy as a proxy for expected utility, there is a clear link between time preference and outcome expectancy in economic theory.…”
Section: Introductionsupporting
confidence: 53%
“…These additional features that support sensemaking should be offered on self-monitoring devices in real-time to help patients understand their data and draw accurate conclusions that lead to behavior change and increased awareness. Recent work has shown that simulated data demonstrating the acute effect of PA on blood glucose may even be enough to change PA-related outcome expectancies and behavioral intentions among adults with T2DM [24].…”
Section: Discussionmentioning
confidence: 99%
“…S1; ref. 33) that demonstrated acute PA (i.e., walking)-related glucose reduction. Next, study staff worked with the participants to calculate their targeted heart rate zone (sex and age adjusted) for light-, moderate-, and high-intensity PA.…”
Section: Pa Education Sessionmentioning
confidence: 99%